Current perspectives and trends in nanoparticle drug delivery systems in breast cancer: bibliometric analysis and review - Sun, Sheng; Wang, Ye-hui; Gao, Xiang; Wang, He-yong; Zhang, Lu; Wang, Na; Li, Chun-mei; Xiong, Shao-quan (Frontiers in Bioengineering and Biotechnology, 2023)
The treatment of breast cancer (BC) is the serious challenge owing to its heterogeneous nature, multi drug resistance (MDR) and the limited therapeutic options. Nanoparticle-based drug delivery systems (NDDSs) represent a promising tool for overcoming the toxicity and chemotherapy drug resistance i n BC treatment. Compared with traditional drug delivery systems (DDSs), the efficacy of NDDSs has been improved, including reduced the dosage of drug and side effects, proper tumour targeting, impr oved bioavailability and drug solubility, controlled drug release. To date, no bibliometric studies have been reported the research landscape of NDDSs-based treatment of BC. In this review, we extracted data from 1752 articles on NDDSs-based treatment of BC published between 2012 and 2022 from th e Web of Science Core Collection(WOSCC) database. VOSviewer, Citespace and some online platfo rms were used for bibliometric analysis and visualisation. Publication trends were initially observed. In terms of geographical distribution, China and USA had the most papers in this subject. The first co ntribution of institutions was Sichuan University. In terms of authorship and co-cited authorship, the most creative author was Yu Zhang. Furthermore, Qiang Zhang and his co-workers had made tremen dous achievements in the field of NDDSs-based BC treatment. The article titled 'Nanomedicine in ca ncer therapy: challenges, opportunities, and clinical applications'had the most citations. Journal of Controlled Release was one of the most active publishers in the field. 'Global cancer statistics 2018: GLOBOCAN estimates of incidence and mortality worldwide for 36 cancers in 185 countries' was th e most cited reference. And we also performed analysis of research hot and cutting-edge research for NDDSs in BC treatment. There were nineclusters: 'tumour microenvironment', 'nanoparticles (drug delivery)', 'breast cancer/triple-negative breast cancer', 'combination therapy', 'drug release (pathwa y)', 'multidrug resistance', 'recent advance', 'targeted drug delivery' and 'cancer nanomedicine'.We also reviewed the core themes of research. In summary, this article reviewed the application of NDD Ss in the treatment of BC.